(untitled) (Research, Society and Development, 2022)
Objective: Map the existing evidence in the literature about strategies to prevent motorcycle accidents involving children. Methodology: Scoping reviews research protocol based on the Joanna Briggs Institute (JBI) manual, following the recommendations of the Prefered Reporting Items for Systematic Review and Meta-Analyses - Extension for Scoping Reviews (PRISMA-ScR) checklist. The guiding question was: What strategies are evident in the literature to prevent motorcycle accidents involving children? Searches will be carried out in the following databases: Web of Science, PubMed, Latin American and Caribbean Literature on Health Sciences (LILACS), IBECS and SciELO. Gray literature will be searched on Open Grey, BDTD, Google Scholar platforms. A search will be carried out with the descriptors of Health Science (DeCS) and Medical Subject Headings (MeSH). The selection of studies will be carried out by two researchers independently and later the organization of the data will be carried out using the Microsoft Excel R program. Los datos se extraerán a través de un formulario elaborado y adaptado a la hoja de trabajo de extracción de datos propuesta por el Instituto Joanna Briggs (JBI). La información a extraer incluye: título, autor(es), tipo de estudio/diseño, año de publicación, país de origen, objetivo, población y muestra, sitio de estudio, principales resultados y recomendaciones.